2003
DOI: 10.1073/pnas.0530289100
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic plasticity in the hippocampus

Abstract: Tests were made for use-dependent plasticity in the cholinergic projections to hippocampus. Transient infusion of the cholinergic agonist carbachol into hippocampal slices induced rhythmic activity that persisted for hours after washout. Comparable effects were obtained with physostigmine, a drug that blocks acetylcholine breakdown and thereby enhances cholinergic transmission. It thus seems that activation of cholinergic synapses induces lasting changes in hippocampal physiology. Two lines of evidence indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 36 publications
(36 reference statements)
2
27
0
Order By: Relevance
“…40), a recent study suggested that cholinergic neurons may also have similar plasticity. Colgin et al (25) showed that endogenous activity of cholinergic pathways in the hippocampus (probably within the field CA3) could induce electrophysiological responses that resembled LTP following brief periods of intense activity. Therefore, the role of cholinergic neurons in learning and memory may involve direct effects besides a modulatory role via glutamatergic synapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40), a recent study suggested that cholinergic neurons may also have similar plasticity. Colgin et al (25) showed that endogenous activity of cholinergic pathways in the hippocampus (probably within the field CA3) could induce electrophysiological responses that resembled LTP following brief periods of intense activity. Therefore, the role of cholinergic neurons in learning and memory may involve direct effects besides a modulatory role via glutamatergic synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were performed on transverse slices of rat brain (male Sprague-Dawley-Harlan, 10-25 days old, n ϭ 6). Standard procedures for preparing and maintaining hippocampal slices (350 m) in artificial CSF (ACSF) were used (25,26). Slices were allowed to recover for at least 1 h, transferred to a submerged recording chamber, and continuously perfused at 2 ml͞min in media (30-32°C).…”
Section: Ex Vivo Long-term Potentiation (Ltp)mentioning
confidence: 99%
“…However, to answer that question we must also understand the molecular mechanisms responsible for the Cholinergic activation in the hippocampus triggers rhythmic activity that can persist for hours and such rhythmic activity is related to both learning and neural plasticity [11]. Furthermore, our recent data demonstrated that when the hippocampal ACh levels are increased in the hippocampus by direct application of physostigmine, the behavioral impairment in spontaneous alternation in PTD rats is eliminated (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal ACh is theorized to facilitate the encoding of new information by simultaneously suppressing excitatory synaptic transmission and enhancing long-term potentiation, while leaving excitatory feed-forward synapses relatively unaffected (Hasselmo et al, 2002). ACh also modulates synaptic plasticity within the hippocampus (Colgin et al, 2003) and long-term potentiation is drastically reduced in genetically engineered mice lacking the mACh M 2 receptor (Seeger et al, 2004).…”
Section: Acetylcholine and Explicit Memorymentioning
confidence: 99%